(untitled) (UNED Research Journal, 2009)
The community development associations in Costa Rica during the 1970s. In 1967 the Legislative Assembly of Costa Rica established the National Community Development Directorate (DINADECO) to support local community development associations, made up of neighbors who shared goals of social and economic improvement for their community. Here I describe and analyze, within the national context, the history of DINADECO between 1968 and 1978, a period in which there were 807 community associations and 26 regional associations. By 1978, 90% of districts had at least one association. The economic results were surprising: the national agricultural added value grew higher than of other Latin American countries pooled. Growth in the added value of industrial production was even greater and more prolonged. But the wealth produced was distributed unequally: 20% of the richest families in the area became 11% richer between 1971 and 1977. But many farmers lost their land and entered in some kind of sub-employment, and 125 000 were forced to emigrate. I propose the new hypothesis that there were multiple communicating and complementary relationships among associations and municipalities in this period. At the end, the deficit accumulated by the model of economic growth brought the end for many development associations in the 1970s. The effect of the decision, made by the Carazo Odio administration (1978), of inserting DINADECO in a Ministry with little political power (Culture Ministry) and of reducing DINADECO’s budget, would be a good topic for future research.